Inflammatory and immunological markers and risk for mortality and cognitive impairment in a longitudinal study of older adults from the longevous project - M.R. Caldeira; C.M. Almada-Filho; M.C. Brunialti; R. Salomão; M.S. Cendoroglo (Archives of Gerontology and Geriatrics Plus)
Senescence of the immunological system is characterized by alterations in immune system cells associated with aging, often linked to cognitive disorders and mortality.Objective:To determine the prevalence of immunological changes, including immunological risk profile (IRP), and its association with cognitive impairments or mortality in oldest-old individuals.Method:A longitudinal study of 201 older adults aged ≥80 years, able to walk unaided, with no cognitive or immunological impairment, and with no serious disease at baseline was conducted. Blood samples were collected at 2-year intervals between 2012 and 2014 during the morning period. High-sensitivity CRP testing was conducted. TCD4 and TCD8 cell counts were performed by flow cytometry and plasma cytokines by CytometricBeadArray (CBA) Human Enhanced Sensitive (BD Biosciences, San Jose, CA, USA) as per manufacturer directions. After the 2-year follow-up, an analysis of associations of test results with cognitive status, as measured by the Mini-Mental State Exam (MMSE), or with mortality, based on medical records and death certificates provided by relatives, was performed. Results:Mean age was 84.4 years.Higher IL6 and hs-CRP levels were observed in deceased participants that weremale (p = 0.016). Higher IL6 levels were associated with cognitive impairment in female participants (p = 0.008). CD4 (p-value <0.001) and CD4/CD8 ratio (p-value = 0.013) decreased, and lower CD4/CD8 values were associated with cognitive impairment in women (p = 0.045).Conclusion:In the independent oldest-old participants with controlled chronic diseases, both men and women aged equally, and not all exhibited inflammation. However, even slight changes in inflammatory markers can be associated with increased risk for mortality and cognitive decline.